The study of perception on islamic banking by non-muslim customers / Tuan Nur Arini Tuan Ibrahim - Tuan Ibrahim, Tuan Nur Arini (2012)
Islamic banking system is gaining popularity among non-Muslims across the worldwide. However, to what extent this statement is true in Malaysian context. Islamic banking gives the optional for customer either Muslim or Non-Muslim to choose which bank that they have interested. According to report provided the percentage of Non-Muslim that prefers using Islamic banking is increasing every year. This study deals with two objectives like to examine the factor that Non-Muslim’s perception toward Islamic banking and to determine the relationship between few factors that drive Non-Muslims with their perception on Islamic Banking, the factors are including the customer’s knowledge, understanding and level of awareness perceived among Non-Muslims. The data collection method that has been used in this research is primary data. While, the techniques were used to answer the research objectives is the qualitative method (questionnaire).The analysis of this research is distribute questionnaire to 100 respondents, all of whom are based in Kota Bharu. These studies only focus to NonMuslim respondents that already have account with Islamic banking. The result of the study showed that Islamic banking services are making headway among Non-Muslim, the higher percentage of respondent in this research is Chinese race. The selection of sample was random picked. The data were collected through self-administered questionnaires distributed by researcher. The data was analyzed by Statistical Packages for Social Science (SPSS) version 17.0. The finding of the study for this research indicate there have positive relationship and significant between non-Muslim customers’ perception of Islamic banking and three factors including knowledge, understanding and level of awareness. The link between customer’s understanding, knowledge and level of awareness could be established with the perception that the establishment of Islamic banking will improve to increase the demand user among Non-Muslim communities. Despite this positive trend, more efforts need to be energized to enhance the level of understanding, knowledge and awareness for non-Muslim customers on the Islamic banking concepts. Most respondents strongly thought that Islamic banking would dominate conventional banking in Malaysia, in the near future. The study also provides evidence that non-Muslims is a vast potential of future growth in Islamic banking if they have knowledge, understanding and awareness